Glimpses of history of the Soviet light industry in Adygea: Maikop sewing factory - N. Z. Kidakoeva; A. A. Kubova (Вестник Майкопского государственного технологического университета, 2025)
The relevance of the research is due to the rise of domestic industry and the tendency to restore light industry in the regions of the country. Despite the great scientific interest in the industry and fashion of the Soviet period, research on the history of the development, formation and functioning of light industry in Adygea has not been carried out, and therefore the chosen topic is very relevant. The problem of restoration and development of light industry, both in the country and in the region, solves a huge layer of economic and social problems of society, one of the main ones is the saturation of the domestic market with high-quality and affordable consumer goods. The goal of the research is a retrospective analysis of the activities of the Maikop sewing factory from the period of creation to the liquidation of the enterprise, based on significant periods of production. The research methods used are structural-functional, historical-genetic, chronological, retrospective, statistical, comparativetypological ones. The results of the research are the first published archival documents on the activities of the Maikop Sewing Factory, as well as the presented retrospective analysis of the factory activities, which makes it possible to assess the contribution of the Adygea sewing industry to the economic development of the region during the period of developed socialism, ensuring a steady increase in the well-being of the people, satisfying consumer demand.As a result of the research, the material on the history of the Maikop Sewing Factory, one of the cityforming enterprises of Adygea, has been systematized and introduced into scientific circulation. The industry began its development with a small hosiery cooperative “Rising Star”, which united various artisans and craftsmen. Over the next seventy years of its existence, the cooperative grew into a large industrial sewing enterprise, the production structure of which had a complete technological cycle. The factory included three branches, the total number of which was more than 2,000 employees. In the mid-1980s, the Maikop Sewing Factory was modernized with new foreign high-performance equipment, which allowed it to increase its industrial potential. The enterprise repeatedly emerged as the winner of socialist competitions at various levels, the factory teams annually participated in internal factory competitions, fulfilling the production plan by 130-140% and always calling on a related team to participate in the socialist competition. The Maikop Sewing Factory had its own brand store, a medical center, two kindergartens and a hostel. This article is a tribute to all the factory employees, and, of course, to the production directors, who throughout the Soviet period of the enterprise’s exis tence served as the very bonds for the entire team: Petr Vasilyevich Petrovsky, Ivan Sergeevich Paliy, Leonid Vasilyevich Fetisov and Lyudmila Kuzminichna Tchaikovskaya.